On Going Beyond the Literal: Translating Metaphorical Conceptualizations in Financial Discourse - Nicaise, Laurent (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This article, through a bilingual French-Dutch corpus, looks at how identical financial-economic concepts are articulated distinctively in the two language communities. The article shows that understanding why an author makes a particular (metaphorical) choice in the lexical repertoire of the discipline could provide language learners and translators with knowledge that will foster their understanding of financial-economic discourse and raise their awareness of ideological, pragmatic and cognitive differences between languages in the role of metaphors. The data indicate that a corpus analysis may contribute to explaining the impact of culture and other communication variables on the lexical realizations of financial-economic concepts in the press.